PROSEDUR SALURAN DISTRIBUSI PUPUK PADA CV. SUMBER AGUNG SANGATTA - Erna Andriani (Tinta Nusantara 2018 Vol.1, 2023)
The aim of this research is to analyze the fertilizer distribution channel procedure at CV. Great Source of Sangatta. The research analysis uses descriptive qualitative, namely in the form of a series of information extracted from the results of the research but are still verbal facts, or still in the form of statements made since preparation before entering the field, during the field and after completion in the field. The results showed that the distribution channels used were indirect distribution channels from producers to consumers.